KONSEP PENCIPTAAN FILM WAYANG HOROR BEKASAKAN - Muhammad Naufal Fawwaz (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2022)
ABSTRACT Bekasakan is a horror movie that uses shadow puppets as the object of its character. This work aims to create a new genre in the shadow puppets of Java, especially in packaging horror themes as special performance plays. Based on puppet performances which were later adapted into a movie perspective, this work is one of the most attractive offers for teh shadow puppets. The novelty of this work is the formation of the demonic figure of Mahakali, which is realized by depicting a strange anatomy of the body and at the same time giving the audience a scary impression. In addition to the formation of the devil Mahakali figure, the application of rules in film is also worked out in such a way as to produce a film work that can give the impression of horror to the audience. It is hoped that the works of secondhand horror puppet films will become an offer or a new style in the world of puppet creativity as well as being a useful contribution to the development of arts and sciences. ABSTRAK Bekasakan merupakan sebuah karya film horor dengan menggunakan media wayang kulit sebagai objek pemerannya. Karya ini bertujuan untuk menciptakan sebuah genre baru dalam dunia pewayangan terutama dalam mengemas tema-tema horor sebagai lakon pertunjukan secara khusus. Berpijak dari pertunjukan wayang yang kemudian diangkat ke dalam perspektif film menjadikan karya ini sebagai salah satu tawaran menarik bagi dunia pewayangan. Kebaruan dari karya ini adalah pembentukan sosok setan Mahakali yang direalisasikan dengan penggambaran anatomi tubuh yang aneh sekaligus memberi kesan seram bagi penonton. Selain terbentuknya sosok setan Mahakali juga penerapan kaidah-kaidah dalam perfilman digarap sedemikian rupa sehingga menghasilkan suatu garap karya film yang dapat memberi kesan horor bagi pernonton. Karya film wayang horor bekasakan diharapkan dapat menjadi tawaran atau gaya baru dalam dunia kreativitas pewayangan sekaligus dapat menjadi sumbangan berguna bagi perkembangan ilmu seni dan ilmu pengetahuan.